The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.jtcvs.2012.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Early outcome of folding mitral valve repair technique without resection for mitral valve prolapse in 60 patients

Abstract: Folding mitral valve repair is an easily fine-tuned technique with a pilot suture, which can be easily removed and repositioned, if unsatisfactory. This reversibility is a significant advantage of this technique. Long-term follow-up is necessary to assess the durability of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…Furthermore, folding technique is also applicable to reduce the redundant leaflets. This technique is similar to that previously reported by Tsukui et al, 16 and although these authors reported good short-term outcomes with this technique, further studies are needed to assess the effects of folding mitral valve repair. We now perform mitral valve repair using mainly the loop technique, and other techniques, as needed (resection and suture, plication, folding) would be added to obtain long-term durability.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, folding technique is also applicable to reduce the redundant leaflets. This technique is similar to that previously reported by Tsukui et al, 16 and although these authors reported good short-term outcomes with this technique, further studies are needed to assess the effects of folding mitral valve repair. We now perform mitral valve repair using mainly the loop technique, and other techniques, as needed (resection and suture, plication, folding) would be added to obtain long-term durability.…”
Section: Discussionsupporting
confidence: 81%
“…[5][6][7][8][9][10][11] The evolution may be due to concerns, such as the stressed cut-through phenomenon of sutures used to approximate the resected leaflet, irreversibility caused by inaccurate leaflet resection resulting in necessary valve replacement, or the timeconsuming complexity of the sliding annuloplasty. The 'respect rather than resect' approach is one of these techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Annular procedures such as annuloplasty sutures or rings are not usually feasible for patients with severe posterior mitral annular calcification. In addition, Woo et al [10] and Tsukui et al [11] routinely applied the similar direction-modified or vertical folding technique and reported favorable mid-term results. With the aid of an annuloplasty ring, the optimal coaptation of the mitral leaflet was achieved by embedding a prolapsing PML into the left ventricle, thereby, resulting in a vertical folding leaflet, and subsequent anatomical morphology equivalent to a triangular resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Additionally, folding valvuloplasty techniques have recently been revisited and are viewed by some as a preferred method of MVP repair, particularly in the setting of minimally-invasive mitral valve surgery. 47 Surgical repair of MVP is effective, durable, and safe: 10-year freedom from reoperation exceeds 90%, and peri-operative mortality approximates 0.5%. 8, 9 However, there are patients who are not candidates for conventional open-heart surgery and cardiopulmonary bypass (CPB).…”
mentioning
confidence: 99%